A New Model for Secondary Prevention of Stroke: Transition Coaching for Stroke - Bushnell, Cheryl; Arnan, Martinson; Han, Sangwon (Frontiers in Neurology, 2014)
Non-adherence to stroke prevention medications is a risk factor for first-ever and recurrent stroke. As of yet, there are no guidelines for processes to recognize and address medication non-adherence in stroke patients. We developed a new model of post-discharge prevention care that measures and addresses medication-taking (TRAnsition Coaching for Stroke or TRACS). TRACS includes personalized education about risk factors and medications prior to discharge, follow-up telephone calls, and appointments with a stroke nurse practitioner (NP). The stroke NP asks about medication use (persistence) and whether doses are missed (adherence), and helps to solve problems with access to medications or side effects. In an analysis of 142 patients enrolled in TRACS from October 2012 to February 2014, medication persistence (use of medications from discharge to the time of measurement) was about 80%. Medication persistence at NP visit was higher in those patients with a first-ever stroke (78.9 %) vs those with recurrent stroke (60.7 %; p=0.045). Concerted efforts with 2-day RN follow-up calls and earlier NP appointments to improve medication-taking behaviors are underway.